STRUKTUR DAN DIKSI TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 4 PARIAMAN - Aulia, Kesi Noferika; Arief, Ermawati (Universitas Negeri Padang, 2019)
ABSTRACTÂ This study aims to describe two things, namely to explain the structure and diction of the report text of the observation results of class VII students of SMP Negeri 4 Pariaman. This type of research is qualitative using descriptive methods. The data from this study are student texts. The data sources used in this study are documents. The instrument of this research is the researchers themselves. Data is analyzed by describing, analyzing, and discussing data based on theory. The results of this study are as follows. First, in writing the text of the report on the observation results of class VII students of SMP Negeri 4 Pariaman, they have used three text structures from the observation report. The structure is a general definition, part description and conclusion. This is evident from all the report texts on observations that have been analyzed, most students have written observational report texts fully using general definitions, part descriptions, and conclusions. Second, judging from the use of diction, students have used diction correctly. From the text analyzed students are more dominant precisely in diction writing, although there are also errors in formation, wrong writing, and the use of incorrect meanings in the observation report text by class VII students of SMP Negeri 4 Pariaman.Â Kata kunci : Â Kualitatif, Menulis, Teks, Struktur, Diksi